2020
DOI: 10.3390/ijerph17062082
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Determinants of Health, Equity, and Dimensions of Health Literacy in Patients with Cardiovascular Disease

Abstract: Background: Health literacy (HL) has been linked to empowerment, use of health services, and equity. Evaluating HL in people with cardiovascular health problems would facilitate the development of suitable health strategies care and reduce inequity. Aim: To investigate the relationship between different dimensions that make up HL and social determinants in patients with cardiovascular disease. Methods: Observational, descriptive, cross-sectional study in patients with cardiovascular disease, aged 50–85 years, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
21
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 40 publications
6
21
1
2
Order By: Relevance
“…The health outcomes obtained in our study would align well with the WHO's social determinants model, which proposes the 'social origin' of diseases, in turn causing health inequalities. Within this framework, HL has shown its central role as a determinant of health [35]. In fact, low levels of education limit access to better jobs, or nudging persons towards less secure and riskier jobs, with lower incomes and poorer levels of health throughout life [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…The health outcomes obtained in our study would align well with the WHO's social determinants model, which proposes the 'social origin' of diseases, in turn causing health inequalities. Within this framework, HL has shown its central role as a determinant of health [35]. In fact, low levels of education limit access to better jobs, or nudging persons towards less secure and riskier jobs, with lower incomes and poorer levels of health throughout life [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…Reflecting the worldwide epidemiological trends of the growing disease burden, care for chronic disease was a critical focus, especially cardiovascular disease [52]. Cabellos-García et al [53] give us new insights in "Relationship between Determinants of Health, Equity, and Dimensions of Health Literacy in Patients with Cardiovascular Disease" in the development of suitable strategies to reduce inequity. In "Health Literacy among People in Cardiac Rehabilitation: Associations with Participation and Health-Related Quality of Life in the Heart Skills Study in Denmark" by Aaby et al [54], the authors help us to understand the associations between health literacy and cardiac rehabilitation outcomes.…”
Section: Individual Level: Prevention and Chronic Carementioning
confidence: 99%
“…Results from empirical studies indicated that higher levels of health literacy resulted in better self-medication decisions and emotional/psychological well-being. Health literacy increases the efficiency and effectiveness of treatments, prevents comorbidities and consequently restores consumer power of choice, autonomy and control over health decision-making (Netemeyer et al , 2020; Cabellos-García et al , 2020; Harzheim et al , 2020; Cabellos-García et al , 2020; McKenna et al , 2020; Liu et al , 2020; Mahmoodi et al , 2019; Abdullah et al , 2019; Nutbeam et al , 2018; Carthery-Goulart et al , 2009; Kripalani et al , 2006).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…As consumers with low health literacy face difficulties in understanding labels and other instructions on medication, this situation represents an indicator of consumer/patient vulnerability and power (Harzheim et al , 2020; Cabellos-García et al , 2020). The inappropriate use of medications may result in negative consequences for the consumer’s health such as inaccurate assessments of disease risks, lower adherence to physician prescription, increasing hospitalization, and mortality and, consequently, health costs (Netemeyer et al , 2020; Visscher et al , 2018; Berkman et al , 2014; Chertman, 2011; Kripalani et al , 2007).…”
Section: Introductionmentioning
confidence: 99%